The Ancient Turkic Book of Reasoning and Revelations "Їrq bitig" of X Century. / El antiguo libro turco de razonamiento y revelación "Ïrqbitig" del siglo X - Kairzhanov, Abay; Shaldarbekova, Azhar (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The article analyzes the texts of legends in the ancient Turkic "The book of reasoning and revelations" ("Їrq bitig"). In order to reveal the implicit text layer of legends there are used methods and techniques of comparative approach, hermeneutics, component analysis, as well as some of the techniques of modern linguistics. Identified different ideological incorporation borrowed from other mythological systems to Turkic environment, which were entered by Silk Road: proto-Sumerian borrowing, ideas of Nestorian Christian, Manichean beliefs, ideas of various kinds of Buddhism, some images from the Mahabharata.RESUMEN El artículo analiza los textos de las leyendas en el antiguo libro turco El libro del razonamiento y la revelación ("Ïrqbitig"). Con el fin de revelar la capa de texto implícito de las leyendas se utilizan métodos y técnicas del enfoque comparativo, hermenéutico, análisis de componentes, así como algunas de las técnicas de la lingüística moderna. Se identificaron diferentes incorporaciones ideológicas tomadas de otros sistemas mitológicos al ambiente túrquico, que fueron incorporadas por la Ruta de la Seda: préstamos proto-sumerios, ideas del cristiano nestoriano, creencias maniqueas, ideas de varios tipos de budismo, algunas imágenes del Mahabharata.